Study on the Dynamic Changes of Landscape Ecological Pattern in Beihai Wetland, Tengchong City - Xu Hongmei; Xi Wujun (E3S Web of Conferences, 2025)
As a critical regional ecological security barrier, understanding Beihai Wetland’s ecological pattern evolution is essential for sustainability. This study used Google Earth Engine (GEE) and Landsat imagery. Applying a hybrid Maximum Likelihood Classification (MLC) and Random Forest (RF) method, it extracted spatial distribution data for Tengchong’s Beihai Wetland across five phases (2009–2024) and analyzed landscape pattern spatiotemporal changes. Results indicate:(1) Wetland area showed sharp non-linear fluctuations, expanding from 26.10 hm² (2009) to 152.46 hm² (2024);(2) Landscape metrics reveal rising heterogeneity: wetland patches became less regular, structural complexity increased significantly, and spatial fragmentation intensified, indicating greater distribution discreteness;(3) Key ecological land declined substantially: forests shrank 8.3% and meadows decreased 40.4% since 2009, directly threatening habitats of endangered Brasenia schreberi and Grus nigricollis. Concurrently, construction land increased 50.3%, showing tourism encroachment on ecological space. These findings provide a scientific basis for building ecological barriers and enhancing sustainable management in plateau wetlands.